Потоково-ориентированная модель многопутевой маршрутизации в MESH-сетях - Гоголева, М. А. (УНДІЗ, 2008)
In this article the flow-based model of multipath routing for MESH-networks is proposed. Model provides the calculation of required set of ways between the given pair of nodes in the network depending on the size of user traffic intensity.
Keywords: Потоковая модель; многопутевая маршрутизация; MESH-сеть